2012
DOI: 10.1038/oby.2012.58
|View full text |Cite
|
Sign up to set email alerts
|

Serial Childhood BMI and Associations With Adult Hypertension and Obesity: The Fels Longitudinal Study

Abstract: Previous studies estimated critical periods of childhood body mass index (BMI) growth and linked these events to adult adiposity and cardiovascular health. We expand upon both results to link childhood BMI growth patterns with adult blood pressure. Data from male and female participants in the Fels Longitudinal Study were used to estimate childhood BMI growth curves, from which we isolate ages of childhood BMI divergence based upon adult BMI and blood pressure measurements. Repeated measure analysis of varianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 5 publications
3
26
0
2
Order By: Relevance
“…Similar results were seen in Sabo et al . (2012), who estimated age of divergences in childhood body size based on adult blood pressure [21]. While this phenomenon may seem to suggest that adult obesity or adiposity are more important in the relationship with cardiac structure than are childhood growth trends, it must be remembered that both childhood obesity and adiposity track into adulthood [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were seen in Sabo et al . (2012), who estimated age of divergences in childhood body size based on adult blood pressure [21]. While this phenomenon may seem to suggest that adult obesity or adiposity are more important in the relationship with cardiac structure than are childhood growth trends, it must be remembered that both childhood obesity and adiposity track into adulthood [42].…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have linked childhood body size measurements with certain cardiovascular outcomes (such as mortality and hypertension), [20], [21] fewer studies have focused on associations between childhood body size and adulthood cardiac structure. Notably, as part of the Bogalusa Heart Study (BHS), Toprak et al .…”
Section: Introductionmentioning
confidence: 99%
“…In another study [21], researchers investigated the association between childhood BP and left ventricular (LV) hypertrophy, a precursor to congestive heart failure. Just as middle-aged BP predicts later LV mass and early adult BP predicts middle-aged LV mass, recent studies have demonstrated that elevated childhood BP and BMI independently determine early-adult LV mass [21,22]. Moreover, a recent observational study [20] has demonstrated that children who improved their BP upon entering adulthood had healthier CIMT compared to those with persistently elevated BP.…”
mentioning
confidence: 99%
“…Excess weight in childhood increases chances of obesity in adulthood 5 . Sabo et al 11 analyzed data on body mass index (BMI) and blood pressure (BP) from individuals during childhood and adulthood. This study identified a higher BP in adults who were obese during their childhood than in those who were eutrophic during that period 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Sabo et al 11 analyzed data on body mass index (BMI) and blood pressure (BP) from individuals during childhood and adulthood. This study identified a higher BP in adults who were obese during their childhood than in those who were eutrophic during that period 11 . Results of some national and international studies have been showing changes in adiposity levels over the years [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%